BERTUMPANG-TINDIHNYA KATEGORI SEJARAH: Analisis Sosio-Historik Sajak-Sajak Sitor Situmorang di Era Reformasi 1998-2005 - Frischa Aswarini, Ni Made (Humanis; Volume 15. No.3. Juni 2016, 2016)
The poetry written by Sitor Situmorang during the Reformation era (1998-2005) reveal complex imbrications of the analytical categories of history such as defined by Kuntowijoyo: traditional-patrimonial, capitalistic and technocratic. Through an analysis of the way Sitor formulates the basic structure of his work, the study aims at deciphering the causality linking those categories. Sitor’s Reformation poetry writing was for this purpose divided into three main themes: spiritualism, nationalism and social awareness. The study applies in turn the theories of inter-textuality, behaviorism and rational choice to successively: identify Sitor Situmorang’s main themes; unravel the complexity of the analytical categories of history; and find out which are the determining factors that underlay this complexity. The study reveals a continuum in Sitor’s ideas between 1948 to 2005. The complexity of the analytical categories of history reflects the complexity of the reality Sitor had to face. Yet this reality did not directly imprint itself. It was instead mediated in a long creative process involving mind, soul and deeds. Sitor would reshape the “base structure” (of a work) with a variety of inputs, some taken from his past, others based on habits or rational considerations, or still reflecting his opinion. The Reformation Era is a very important period for Sitor as an exile and as a human being, haunted by a deep feeling of physical and spiritual alienation. Sitor’s poetry represents both the history of his thoughts and the history of Indonesia.
Keywords: Poetry of Sitor Situmorang, Reformation, Historical Categories